The evolutionary consequences of genetic adaptation to parasitism - Whiting, James R. (2018)
The processes driving and maintaining variable immune responses are poorly understood compared with other aspects of an organism’s ecology. This is particularly true from an evolutionary perspective, as the evolutionary relationships between immune responses and other traits and processes in nature remain inadequately explored. I investigated these associations in this thesis using the three-spined stickleback system as an evolutionary and immunological model. I combined sampling of wild individuals with genomic analyses to demonstrate phenotypic and genomic associations between immune responses and life history evolution across multiple populations. I also observe how experimental changes in daylength, a seasonal cue, modulate immune responses and increase parasite susceptibility in a controlled laboratory experiment. These findings occur independently of natural variation in parasite resistance. Stickleback are also a model for studies of speciation. I used sampling of wild hybrids to assess the significance of immune variation in postzygotic isolating mechanisms between diverging ecotypes; although my findings suggest a minor role. Finally, I demonstrate that genomic responses to parasitism and abiotic environmental variation are repeatable across independent, intercontinental adaptive radiation events in sticklebacks; conferring a repeatability of the evolutionary relationships of immune variation documented in this thesis. The findings within this thesis therefore provide novel insights into poorly explored or open areas of research regarding how variable immune responses evolve in nature.